PENGARUH AUDIT DELAY, REPUTASI DAN KOMPLEKSITAS OPERASI TERHADAP TIMELINESS PELAPORAN KEUANGAN PERUSAHAAN PERTAMBANGAN TAHUN 2012-2016 - Mr Sujarwo (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Investors don't want to lose opportunities, and the answer is looking at the financial statements. Therefore, reporting companies are not just paper, but proof of trust in investors. This study aims to determine the effect of audit delay, reputation auditor and the complexity of the company's operations against timeliness of financial reporting. This research is a quantitative research using secondary data obtained from Indonesia Stock Exchange (IDX) during period 2012-2016. Population in this research is mining company listed in Bursa Efek Indonesia. The sample of this research consist of 20 mining companies listed in Indonesia Stock Exchange 2012-2016 which is determined by purposive sampling. Data analysis technique used is logistic interpretation using SPSS version 22. The result showed (1) Audit delay has significant effect on financial reporting timeliness, (2) Auditor's reputation has no significant effect, (3) Complexity of the company's operations has no significant effect, and (4) Audit delay, auditor reputation and company operating complexity simultaneously significant timeliness of financial reporting